Avaliação da aprendizagem de alunos com deficiência intelectual no AEE da Associação Pestalozzi de Fortaleza-CE pelo ensino remoto em tempos de pandemia (2020-2021) - Mendonça, Andréia Vieira de (2022)
The historical course reveals, in addition to stigmas and prejudices, which still persist today, an ancient battle of the person with disabilities to guarantee their fundamental rights, which has repercussions on the vast legal framework to guarantee Inclusive Education and standardize its practice, a challenge even today, which was enhanced in the face of pandemic times (2020- 2021), causing profound distortions to emerge in the learning assessment process, which has been constituted in the exercise of classification, selection and exclusion, as opposed to the formative character. Considering the teaching-learning assessment as a pedagogical component that facilitates learning, the general objective of this research was to investigate the practice of teaching-learning assessment of students with intellectual disabilities, in the Specialized Educational Service (AEE) of the Pestalozzi Association of Fortaleza-CE, during the Covid-19 pandemic (2020-2021). Specifically, it aimed to: i) identify teachers' conceptions about intellectual disability and teaching-learning assessment; ii) research the evaluation procedures and instruments used by AEE teachers with students with intellectual disabilities, during the Covid-19 pandemic (2020-2021); iii) to know the difficulties related to the teaching-learning assessment of students with intellectual disabilities through AEE teachers, students and their families or guardians during this period and iv) to collect suggestions from teachers, students and their families or guardians, for the improvement of educational changes and the construction of systematic and reflexive evaluation practices. With this intention, a qualitative research was carried out, in the form of a case study. The data collection instrument was the semi-structured interview for all elements of the sample. The data obtained were categorized according to content analysis. The samples consisted of 2 teachers from AEE, from the Pestalozzi Association of Foretaleza-CE, 5 family members or guardians of students with intellectual disabilities and 5 students with intellectual disabilities, totaling 12 subjects. The results revealed that the teachers pointed to practical conceptions about intellectual disability and the evaluation of teaching and learning, compiled from the perspective of promoting individual advances for the target audience of Special Education, through AEE resources. The difficulties highlighted by the subjects relate to issues related to the context of the Covid-19 pandemic, which involve accessibility to technological resources, socio-emotional conditions to accompany the care and the invisibility of the singularities of people with intellectual disabilities, within the scope of Inclusive Education, which proved to be a process still under construction.